2018
DOI: 10.15376/biores.13.3.5711-5724
|View full text |Cite
|
Sign up to set email alerts
|

Physical, tensile, and biodegradability properties of cross-linked polyvinyl alcohol/palm kernel shell powder biocomposites

Abstract: Polyvinyl alcohol/palm kernel shell powder biocomposites were prepared by using a solution casting method. To enhance the properties, the crosslinking agent glutaraldehyde (GA) was added to the composition. The effect of the crosslinking agent on the biocomposite was studied based on the change in the tensile properties, physical properties, and biodegradability. The optimum GA content was found to be 2 phr because the tensile properties tended to decrease with higher GA contents. The water absorption percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…The films underwent swelling and shrinkage when buried in the soil, which caused a rougher surface and cracking of the surface of the films depending on the soil humidity [34][35][36]. The SEM results are consistent with the visual appearance evaluation and weight loss measurement, where the films in compost soil degraded faster than the films buried in planting soil.…”
Section: Surface Morphology Of the Filmssupporting
confidence: 80%
“…The films underwent swelling and shrinkage when buried in the soil, which caused a rougher surface and cracking of the surface of the films depending on the soil humidity [34][35][36]. The SEM results are consistent with the visual appearance evaluation and weight loss measurement, where the films in compost soil degraded faster than the films buried in planting soil.…”
Section: Surface Morphology Of the Filmssupporting
confidence: 80%
“…However, reduced ductility and moisture resistance were observed in all weight fractions studied. Similarly, in Omar et al (2015), though the inclusion of PKS into the composite reduced the degree of crystallinity from 34.8 % to 31.7 %, yet silane treatment of the PKS made a significant improvement in the thermal stability by up to 37.6 % crystallinity at almost the same melting point of about 163 • C. Alias et al (2018), made a biocomposite with PKS ash reinforced in a polyvinyl alcohol matrix. Results showed that at 30 % weight fraction of PKS in the composite, the stiffness increased from about 95 to 330 MPa with about 21.62 % rise in biodegradability at 40 % PKS.…”
Section: Use In Polymer Compositesmentioning
confidence: 98%
“…Remarkably, a peak appears in the 3434 cm − 1 wavelength and is consistent in the raw PKS, as well as in the PKS-activated carbon when compared with the commercially obtained activated carbon. This was considered as a stretched vibration from hydroxyl ion (-OH) as a result of absorbed moisture (Rashidi et al, 2020;Ang et al, 2020;Jitjamnong et al, 2020;Abdullah et al, 2020) and hence responsible for the biodegradability of the PKS (Alias et al, 2018). In addition, the FTIR spectra for activated carbons from both PKS and commercial source had four peaks each, therefore implying a comparable quality.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…This indicates a change in the functional group and a shift in the wavenumber of the MSGPvA BtC if the MSGPvA BtC is added with PCL and AMA. Alias et al (2018) explained that the formation of a composite film from a polymer with PVA caused a shift in the wavenumber of the hydroxyl group of PVA from 3,279.10 to 3,278.67 and 3,260.93 cm −1 .…”
Section: Functional Groupsmentioning
confidence: 99%